ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS DENGAN STRUKTUR MODAL SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2019 - Iskandar Muda Situmorang (Jurnal Ilmu Manajemen METHONOMIX, 2022)
This study aims to determine and analyze the effect of Liquidity, Receivables Turnover and Profit Growth on Profitability with Capital Structure as a moderation variable. This population is 594 companies. The sampling method used in this study was a purposive sampling method and obtained as many as 211 companies with observational data of 633 companies. This research data was obtained from the financial statements of non-financial companies listed on the Indonesia Stock Exchange from 2017-2019. The research method used is a structural equation model with the IBM AMOS 2 program. The results of the sub-structural equation analysis show that Profit Growth has a positive effect on Profitability while Liquidity and Receivables Turnover do not affect profitability through the Capital Structure as a Moderation variable in Non-Financial companies listed on the Indonesia Stock Exchange for the 2017-2019 period.